Use of preventive measures against milk fever in Punjab, Pakistan - Zaidi, Syed Ahad Raza (SLU/Dept. of Animal Nutrition and Management (until 231231), 2016)
Milk fever or hypocalcaemia is widely acknowledged disease of dairy animals at the time of parturition. The study was aimed to investigate preventive strategies against milk fever by small and large farmers in Punjab, Pakistan from the year 2011-2013. For the sample 212 farmers consented to be part of this study, a questionnaire survey was used as a tool for data collection. The sample was categorized as small (less than 10) and large herd size and data was divided into “no milk fever” and any milk fever” groups, then analyzed through chi square and logistic regression by Statistical Analysis Software (SAS). This study concluded that farmers in Punjab, Pakistan focused on few milk fever preventive methods i.e. administration of Vitamin D, milking strategy, oral prophylaxis (oral calcium intake) and feeding strategy. From these methods; oral prophylaxis came out as the most widely used strategy among farmers, but it was highly used in both risk groups with or without milk fever therefore statistically it didn’t impacted any significant effect. Milking strategy as preventive measure; showed the significant higher use among farmers with no milk fever (p = 0.001). Statistical analysis also presented, use of Vitamin D as prophylactic method; was used more in herds with no milk fever. Logistic regression of other risk factors revealed that herds with buffalos have a tendency for higher risk of having milk fever (p<0.09)